The Effective Way to Develop Speaking Skills - Angela M Sihotang; Friskila Sitanggang; Novitriani Hasugian; Erikson Saragih (Institut Agama Islam Negeri Palopo, 2021)
Speaking is the skill of conveying messages through spoken language, by speaking so that the fulfillment of the need to communicate with the surrounding, environment based on initial observations with people around speaking skills is still lacking.The low ability to speak with the results of interviews with people around it’s caused by internal factors and external factors that come from their techniques in obtaining and applying theories regarding speaking skills. Interview techniques with certain topics are an attempt to improve speaking skills to describe something, give opinions and tell stories is the way to approach the object. The benefits of this research include theoretical and practical benefits, theoretically, the results of this study are expected to contribute knowledge related to the use of appropriate techniques in learning to speak, practically the results of this study are expected to be useful for the author as the development of knowledge in the field of speaking skills. This study used a random design with people around, data collection was done by interviewing the non-test data collection tools used were interviews and observation. The data analysis was done qualitatively. The conclusion of this research is to add the knowledge about what is the effective way to develop speaking skills and the author hopes all the readers can get the aim from this research.